Involvement of DNA gyrase in bacteriophage T7 growth. - Steck, T R (1985)
We have found that the burst size of bacteriophage T7 was decreased in two Escherichia coli temperature-sensitive gyrase mutants incubated at the restrictive temperature. This reduction in burst size indicates that gyrase may be required for T7 growth.